The effects of expanding education on the distribution of income in Ceará: A microsimulation - Francisco H. G. Ferreira; Phillippe George Leite (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Does more education really mean less poverty and less inequality? How much less? And what are the transmission mechanisms? This paper presents the results of a microsimulation exercise for the Brazilian State of Ceará, which suggests that broad-based policies aimed at increasing educational attainment would have substantial impacts on poverty reduction, but muted effects on inequality. While these results are highly dependent on assumptions about the behaviour of returns to education for the distribution of earnings, they are much more robust for the distribution of household income per capita. Over half of the poverty reducing effect of more education operate through greater incentives for labour force participation among the poor, and through reductions in fertility. Both of these effects operate largely through decisions made by poor women. – education ; poverty ; inequality
Keywords: C15; D31; I31; J13; J22; 330; Bildungsniveau; Bildungspolitik; Armut; Einkommensverteilung; Ceara